Childhood explanatory factors for adolescent offending: a national comparison based on official records in London, Pittsburgh, and Zurich - Zych, Izabela (Journal of developmental and life-course criminology, 2021)
This study compares childhood explanatory factors for adolescent offending according to official records obtained in three longitudinal projects conducted in three different countries: the Cambridge Study in Delinquent Development, the Pittsburgh Youth Study, and the Zurich Project on the Social Development from Childhood to Adulthood. This is the first comparison of a great variety of explanatory factors for recorded offending measured in three different geographic areas and different generations. Several common explanatory factors were found in the three projects, and they seem to be generalizable across time and context. Common explanatory factors for offending included individual factors such as high impulsivity, attention deficit, and low school achievement. Childrearing explanatory factors included poor supervision, physical discipline, and parental conflict. Socioeconomic explanatory factors included low family income and divorced parents. Parental imprisonment was also a common risk factor among the three studies. Replicable childhood predictors of youth offending should be targeted in prevention.